Street Food in Relation to Consumers Health Status in Selected Locations of Dhaka Metropolitan City - Jahan, Khursheed; Al Mamoon, AB; Mannan, MA; Chowdhury, Shamsi Ara (Bangladesh Journal of Nutrition, 2010)
Bangladesh Journal of Nutrition Vol.17 2004 p.43-50